Optimalisasi working memory siswa melalui desain worked example berbasis cognitive load theory pada materi SPLDV - Pratama Wahyu Purnama; Indah Nikmatul Hidayati (FKIP Universitas Mataram, 2025)
Systems of Linear Equations with Two Variables (SPLDV) contain numerous symbols and present high complexity in their solution processes, which can create substantial cognitive demands for middle school students. Instructional design that minimizes irrelevant cognitive load while optimizing schema formation is essential to accommodate the limited capacity of working memory. Cognitive Load Theory (CLT) offers effective strategic alternatives for managing cognitive load during learning, particularly in reducing extraneous cognitive load. One recommended approach is the implementation of worked example strategies. This article focuses on developing a worked example design for SPLDV material based on CLT principles. The research comprises three phases: examining the cognitive load of SPLDV content, reviewing fundamental CLT principles, and constructing instructional design using worked example strategies. The research produces a worked example design featuring structured solution steps that eliminate split attention and redundancy effects, successfully reducing extraneous cognitive load and enhancing working memory effectiveness in learning SPLDV. These findings can serve as a foundation for further design development or empirical validation in broader educational contexts.